Neuroleptic Malignant Syndrome Requiring Neurological Intensive Care Unit Follow-up: Review with Nine Cases - Nazlı Gamze Bülbül; Yaprak Seçil; Yeşim Beckmann; Tülay Kurt İncesu; Galip Akhan (Galenos Yayinevi, 2014)
Neuroleptic malignant syndrome (NMS) is a rare but life-threatening clinical manifestation induced by neuroleptic medication. Although NMS is regarded as a psychiatric diagnosis, its treatment requires a systematic approach and thus intensive care follow-up. In this paper, we report nine cases with NMS followed up in our Neurology Intensive Care Unit over the last three years.